Is single-port video-assisted thoracic surgery for mediastinal cystectomy feasible? - Nanqing Jiang; Yiming Lu; Jun Wang (Journal of Cardiothoracic Surgery, 2019)
Abstract Background Video-assisted thoracic surgery (VATS) for mediastinal cysts has been used with increasing frequency. Both single-port VATS and three-port VATS procedures are used for mediastinal cystectomy. Few studies have been published to compare three-port VATS and single-port VATS procedures in mediastinal cystectomy. Methods Forty-five patients with mediastinal cysts who underwent single-port procedures (n = 23) or three-port procedures (n = 22) in our department from January 2016 to July 2018 were retrospectively analysed. The perioperative conditions and pathological findings were analysed. Results The single-port group showed shorter operation times [45 (35–60) vs 55 (45–80) min, p = 0.013], less retention time of the thoracic drainage tube [27(24–48) vs 48(48–70) p < 0.001)], shorter postoperative hospital stays [5(4–6) vs 7(5–7), p = 0.011] and less costs [2.0)1.2–2.5) vs 2.5(1.9–3.5), p = 0.032] than those of the three-port group. No difference was found in case conversions to open procedures (p > 0.99) or second operations (p > 0.99). Logistic regression analysis showed that the surgical method (p = 0.426) and surgeon experience (p = 0.719) were not independent prognostic factors for the success of surgery. Conclusions The single-port VATS procedure was not inferior to the three-port VATS procedure for mediastinal cystectomy. The single-port VATS procedure is a feasible choice for mediastinal cystectomy.